Validity Of Goods And Services Sale And Purchase Agreements By Online (E-Commerce) - Aldi, Muhammad; Hidayati, Rahmatul; Sunardi, Sunardi; Parmono, Budi (Universitas Islam Malang, 2024)
Abstract : The internet is developing quickly and has a big impact on every part of life. People may contact, communicate, and even conduct business with anyone worldwide quickly, cheaply, and effortlessly thanks to the internet. In actuality, buying and selling transactions through electronic media are really legal agreements or relationships that are carried out through the networking of computer-based information systems and communication systems based on telecommunications networks and services. This process is further made possible by the existence of worldwide internet computer networks. International society in general and Indonesian society in particular have greatly benefited from the use of electronic transaction media, or e-commerce, in the trade industry. The establishment of an agreement occurs when two parties come to a consensus on a primary issue that serves as the agreement's goal. To agree on what has been agreed upon, both parties must be present in a meeting of wills. It is possible to comply with wishes orally or in writing. In today's world, where technology is widely used in business, a face-to-face meeting or written agreement are no longer necessary for the expression of wants. Agreements between parties with different legal systems that are made online are nonetheless enforceable.